Geant4 simulation of a conceptual calorimeter based on secondary electron emission - Ozok, F.; Yetkin, T.; Yetkin, E. A.; Iren, E.; Erduran, M. N. (IOP PUBLISHING LTD, 2017)
We present a conceptual sampling electromagnetic calorimeter based on secondary electron emission process. The secondary electron emission process was implemented in Geant4 as a user physics class, which accurately reproduces the energy spectrum and yield of secondary electrons for thin metals. The simulation results for the response linearity and energy resolution are compared with that of a scintillation calorimeter. The response and energy resolution of the calorimeter were obtained for electron energies up to 50 GeV. The response linearity to electromagnetic showers is to within 1.5%, whereas the energy resolution is sigma/E = (44%) GeV1/2/root E for 2.5 cm sampling of iron absorber.
Keywords: Detector modelling and simulations II (electric fields, charge transport, multiplication, and induction, pulse formation, electron emission, etc); Calorimeter methods; Electron multipliers (vacuum); Vacuum-based detectors; ELECTROMAGNETIC SHOWERS; MICROCHANNEL PLATES; PARTICLES; DETECTOR; COPPER; Instruments & Instrumentation